PENGARUH REKRUTMEN, SELEKSI, KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MERPATI MAINTENANCE FACILITY SIDOARJO - Gunawan, Kridho Hery; Permatasari, Adinda; Nindiyani, Sistha Alim (JEM17: Jurnal Ekonomi Manajemen, 2021)
The purpose of this study was to examine and analyze the effect of recruitment, selection, communication, motivation and work environment of employees at the aircraft engineering department of PT. Merpati Maintenance Facility Sidoarjo. The sample in this study amounted to 82 employees through the distribution of questionnaires. The type of data used is quantitative. The time of the study was carried out in May-June 2021. The data processing in this study used IBM SPSS Statistics version 25. The results of the t-test showed that the variable sig motivation (X4) and work environment (X5) <0.05, then H0 was rejected at a significance level of 5%. It can be concluded that the motivation variable (X4) and work environment (X5) partially have a significant and positive influence on employee performance (Y). While the variable recruitment (X1), selection (X2), communication (X3) > 0.05, then H0 is accepted at a significance level of 5%. It can be concluded that the variables Recruitment (X1), selection (X2), communication (X3) partially have a significant and negative influence on employee performance (Y) in the aircraft engineering section of PT. Merpati Maintenance Facility Sidoarjo. Variables Recruitment, Selection, Communication, motivation and work environment simultaneously have a significant effect on employee performance in the aircraft engineering section of PT. Merpati Maintenance Facility Sidoarjo with a significance value of 0.001 < 0.05. The results of the coefficient of determination show a value of 0.175 or 17.5%, which means that all independent variables (recruitment, selection, communication, motivation and work environment) can affect employee performance variables by 17.5% while the rest is influenced by other variables besides the independent variables in the study. this amounted to 82.5%.